Determination of the quantity of sodium and potassium in organic and industrialized baby papers (Research, Society and Development, 2020)
The consumption of baby food for children's line grows over the years and has gained more and more prominence in the Brazilian market due to its great practicality. In parallel, there is a significant increase in the excessive intake of sodium and potassium by consumers, also due to the high intake of industrialized products. Thus, this work aimed to quantify the sodium and potassium content in baby food, using the method of flame photometry, in twenty-seven samples of baby food from three different brands marketed in the city of Chapecó / SC. For research, industrialized baby food and organic baby food were used. The results were subjected to analysis of variance (ANOVA) and then to the Tukey means comparison test at a significance level of 5% (p